Interpretive Diagnostic Error Reduction: Guideline Update from the College of American Pathologists in Collaboration With the Association of Directors of Anatomic and Subspecialty Pathology - Suzanne M. Dintzis; Juanita J. Evans; Marisol Hernandez; Tanja Kalicanin; Christina Lacchetti; Raouf E. Nakhleh; Christopher N. Otis; Liron Pantanowitz; Vinita Parkash; Stephen S. Raab (Archives of Pathology & Laboratory Medicine, 2026)
Context.— In 2016, the College of American Pathologists published an evidence-based guideline to develop recommendations for interpretive diagnostic error reduction in anatomic pathology. New evidence, together with evolving practice environments and the continued adoption of digital technologies, including artificial intelligence, has prompted a review of the guideline. Objective.— To assess evidence published since the release of the original guideline and update evidence-based recommendations for the reduction of diagnostic errors. Design.— The College of American Pathologists, in collaboration with the Association of Directors of Anatomic and Subspecialty Pathology, convened a panel of experts to update the 2016 evidence-based guideline. A systematic literature review was conducted to address 4 key questions. Using the Grading of Recommendations Assessment, Development and Evaluation approach, recommendations were created based on the available evidence, certainty of that evidence, and key judgments as defined in the Grading of Recommendations Assessment, Development and Evaluation framework. Results.— Two strong recommendations and 4 good practice statements were established for the reduction of diagnostic error. Conclusions.— The expert panel recommends that anatomic pathologists implement procedures for the review of pathology cases to detect and correct potential interpretive errors to improve patient outcomes.